2017
DOI: 10.1155/2017/3058569
|View full text |Cite
|
Sign up to set email alerts
|

Genital Tract Infections in an Isolated Community: 100 Women of the Príncipe Island

Abstract: Objective To characterize the vaginal microbiome and the rate of sexually transmitted infections (STIs) in the women of Príncipe (São Tomé and Príncipe). Methods Cross-sectional study of 100 consecutive women, invited for a free appointment and cervical cancer screening. A vaginal slide (wet mount microscopy) and a cervical sample (ThinPrep®) (Pap test, high risk human papillomavirus [HR-HPV], N. gonorrhea [NG], T. vaginalis [TV], and C. trachomatis [CT]) were obtained. Results TV, NG, CT, and HIV were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
12
2
1
Order By: Relevance
“…A similar pattern was noted in other studies, wherein fungal agents were most prevalent, followed by Trichomonas species. [8][9][10][11][12] As mentioned earlier, the number of specific infectious agents detected was lower in modified compared to conventional CS samples; this reduction was noted in almost all infectious agents, except HSV. This finding has been supported by other researchers.…”
Section: Discussionmentioning
confidence: 96%
“…A similar pattern was noted in other studies, wherein fungal agents were most prevalent, followed by Trichomonas species. [8][9][10][11][12] As mentioned earlier, the number of specific infectious agents detected was lower in modified compared to conventional CS samples; this reduction was noted in almost all infectious agents, except HSV. This finding has been supported by other researchers.…”
Section: Discussionmentioning
confidence: 96%
“…Global prevalence (symptomatic and asymptomatic) varies widely according to the population studied (12-55%), being consistently higher in black women (50-55%) [86,87]. BV is much rarer in non-sexually experienced women, especially in those without any kind of sexual contact [88], but is very high (20-50%) in women with female partners [89].…”
Section: Bacterial Vaginosis (Bv): Breaking the Mythsmentioning
confidence: 96%
“…Among gynaecological complications, there are studies relating it to an increased risk of having an abnormal Pap test and of acquiring STIs. The presence of inflammation and erosions, the lack of lactobacilli, and the associated increased levels of sialidase can easily explain the increased risk for STIs; diagnosing and treating AV can be highly relevant in populations at elevated risk, namely in Africa [87,118].…”
Section: Complicationsmentioning
confidence: 99%
“…Previous studies have shown that AV is associated with miscarriage,6 increased risk of amnionitis,7 placental histological inflammation,8 premature rupture of membranes,9 preterm delivery,6,10 foetal funisitis,8 and major cervical cytological abnormalities 11,12. The prevalence of AV is reported to be 5–27.6% in various areas 6,9,1217. Thus, it is vital to identify AV so that standardized treatments can be developed to avoid complications.…”
Section: Introductionmentioning
confidence: 99%